The Digital Teaching Landscape: Investigating the Roles of Interest, Self-Efficacy, and Experience in Shaping TPACK - Salsabila , Sarah; Rahmatullah, Bahbibi; 'Aziz, Hafidh (Islamic Early Childhood Education Study Program, Faculty of Tarbiyah and Education, UIN Sunan Kalijaga Yogyakarta, 2023)
Purpose –This study aims to analyze the relationship between interest, self-efficacy, and practical teaching experience concerning prospective early childhood education teachers' perceptions of Pedagogical Knowledge of Technology Content. Design/methods/approach – This research employs an associative correlational quantitative design, involving 84 students from the Early Childhood Islamic Education Study Program at UIN Sunan Kalijaga Yogyakarta. Data was collected through both offline and online questionnaires and analyzed using multiple linear regression techniques. This analysis assesses the predictive capacity of interest, self-efficacy, and teaching experience in determining TPACK within the perceptions of prospective ECCE teachers. Data analysis was aided by the statistical software SPSS 26 for Windows. Findings – The statistical tests indicate that interest, when considered individually, does not exhibit a positive and significant effect on TPACK. Conversely, self-efficacy and teaching practice experience, when examined separately, demonstrate a positive and significant influence on TPACK. Moreover, when these variables are collectively examined, interest, self-efficacy, and teaching practice experience collectively impact TPACK, showcasing a robust relationship of 75.4%. However, it's worth noting that there are some inconsistencies in the results concerning the impact of interest on TPACK, which may be attributed to a lack of specific context and a detailed examination of respondents' interest levels. Research implications/limitations – This study primarily focuses on elucidating the interplay between interest, self-efficacy, and practical teaching experience in TPACK development. Practical implications – These practical implications are envisioned to enhance the quality of early childhood education and prepare prospective ECCE teachers to confront the evolving technological landscape. Originality/value – This research contributes to an enhanced understanding of the interrelationships between interest, self-efficacy, and practical teaching experience in shaping prospective teachers' perceptions of TPACK, offering novel insights into the professional development of prospective ECCE teachers. Paper type Research paper